PERAN MEDIA SOSIAL SEBAGAI RUANG PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK SPIRITUALITAS PESERTA DIDIK DI ERA TRANSFORMASI DIGITAL - Melvin Subay (Metanoia, 2026)
Abstract Digital transformation has significantly changed the learning patterns of younger generations, including the development of students’ spirituality through social media as a space for informal learning. This study aims to analyze the role of social media in shaping students’ digital spirituality within the context of Christian Religious Education in the era of digital transformation. The research employed a qualitative approach using a literature review method through the analysis of scholarly articles, academic books, and relevant studies related to social media, informal learning, and digital spirituality. The findings reveal that social media functions as an informal learning ecosystem that enables students to gain spiritual experiences through the consumption of religious content, faith reflection, and participation in digital communities. Social media also provides flexible, participatory, and contextual learning access that aligns with the characteristics of the digital generation. However, several challenges were identified, including superficial faith understanding, theological misinformation, and the dominance of digital algorithms. Therefore, Christian Religious Education needs to develop reflective, critical, and contextual pedagogical approaches so that social media can be utilized optimally in fostering students’ digital spirituality in a deeper and more transformative manner. Abstrak Transformasi digital telah mengubah pola pembelajaran generasi muda, termasuk dalam pembentukan spiritualitas siswa melalui media sosial sebagai ruang pembelajaran informal. Penelitian ini bertujuan menganalisis peran media sosial dalam membentuk spiritualitas digital siswa dalam konteks Pendidikan Agama Kristen pada era transformasi digital. Penelitian menggunakan pendekatan kualitatif dengan metode kajian literatur melalui analisis berbagai artikel ilmiah, buku akademik, dan penelitian relevan mengenai media sosial, pembelajaran informal, dan spiritualitas digital. Hasil penelitian menunjukkan bahwa media sosial berfungsi sebagai ekosistem pembelajaran informal yang memungkinkan siswa memperoleh pengalaman spiritual melalui konsumsi konten rohani, refleksi iman, dan partisipasi dalam komunitas digital. Media sosial juga memberikan akses pembelajaran yang fleksibel, partisipatif, dan kontekstual sesuai karakteristik generasi digital. Namun, ditemukan tantangan berupa dangkalnya pemahaman iman, disinformasi teologis, dan dominasi algoritma digital. Oleh karena itu, Pendidikan Agama Kristen perlu mengembangkan pendekatan pedagogis yang reflektif, kritis, dan kontekstual agar media sosial dapat dimanfaatkan secara optimal dalam membentuk spiritualitas digital siswa secara mendalam dan transformative.